Cardiac related mortality trends in Forensic Department of Hospital Serdang, Selangor, Malaysia - Ahmad, Zalinah; Blin, Joan; Mohtaruddin, Norhafizah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Cardiovascular disease (CVD) is the principal cause of admission and death in the Malaysian government hospitals. Method: The pattern of cardiac related mortality (CRM) cases in Hospital Serdang, Selangor was reviewed to determine the specific trends in ethnicity, age, gender and type of CRM. Data was drawn from the death registry records in Forensic Department of Hospital Serdang from January 2006 to December 2008. This preliminary project was carried out to assess the number of CRM cases and their characteristics to feed the decision to sensibly embark on another project related to atherosclerosis. Results: Out of 573 CRM cases, 84.5% were Malaysians out of which the majority were Malays (45.9%), followed by Chinese (30.2%), and Indians (22.1%). The majority were men (78.4%) with a mean age of death at 51.83 ± 14.10 (95% CI 50.52-53.14) years as compared to women (21.6%) with a mean age of death at 57.42 ± 16.92 (95% CI 54.41-60.43) years. Declining mortality trend was observed only in men. The 46-60 years old age group had the highest percentage of mortality and continually increase by year. Ischaemic heart disease (IHD) was the most common CRM type (69.1% in 2006, 66.2% in 2007, and 71.9% in 2008). Conclusion: We observed inconsistent trends of CRM in Hospital Serdang in terms of ethnicity, age, gender and type of CRM cases presented. Nevertheless, these findings do not necessarily represent the overall trends of CRM in Malaysia.